New record of Paralomis spinosissima Birstein & Vinogradov (Decapoda: Anomura: Lithodidae) from Mar del Plata, Argentina - OLGUÍN, NICOLE; OCAMPO, EMILIANO H.; FARIAS, NAHUEL (Zootaxa, 2015)
The lithodid crab Paralomis spinosissima is previously known only in Sub-Antarctic waters from South Georgia Island to the Drake Passage. Here we recorded a juvenile male obtained off shores of Mar del Plata (~37°S), Argentina. This new occurrence extends the distribution range of the species over 1300 km northwards in the Atlantic Ocean.